COVID-19 and Acute Pancreatitis: Not Increased Risk but Reduced Care - Michele Cevolani; Marco Ferronato; Chiara Elide Lizzio; Eleonora Elia; Desy Marini; Elena Mazzotta; Claudio Ricci; Riccardo Casadei; Marina Migliori (Gastroenterology Insights, 2023)
Background and aim: Over the last few years, SARS-CoV-2 has been reported as a possible cause of acute pancreatitis (AP), but whether it is a relevant clinical–epidemiological entity is still a matter of debate. We aim to evaluate the epidemiological characteristics of AP during the first year of the COVID pandemic (2020) and compare them with the pre-COVID period (2008–2019) to identify any differences and clarify a potential causative role of SARS-CoV-2. Methods: We used a monocentric retrospective study of 132 AP patients during 2020 and 1987 AP patients during 2008–2019. Diagnosis and severity were classified according to the revised Atlanta criteria. Propensity score matching was performed according to clinical–epidemiological features, and outcome analysis was performed on two subgroups of 109 patients. Results: The total number of AP cases in 2020 is one of the lowest in the last 13 years (132 cases, median 161, IQR 146-183). No major epidemiological differences were noted. During 2020, we observed a significant modification of the distribution of etiologies (p < 0.001), mainly based on a decrease in biliary forms (59.6% vs. 43.2%) and an increase in alcoholic forms (6.9% vs. 12.9%). Idiopathic forms remain unchanged (20.5% vs. 21.9%). The proportion of AP of idiopathic etiology and SARS-CoV-2 infection was 0.008%. There were no differences in terms of severity distribution (p = 0.127), length of stay (p = 0.916), need for ICU (p = 0.139), or mortality (p = 0.462). Even among statistically matched groups, there were no differences between the length of stay (9 vs. 10 days, p = 0.890), need for ICU admission (1.8% vs. 3.7%, p = 0.683), or in-hospital mortality (0 vs. 1.8%, p = 0.342). Conclusions: The lower AP diagnoses indicate delayed and likely missed diagnoses, probably because of both hesitancy and organizational problems during the pandemic. The unchanged proportion of idiopathic forms supports the hypothesis that SARS-CoV-2 is not an AP trigger.